Are we ready for an inclusive classroom?: school administrators' and teachers' perceptions of autism - Akgul, Esra Macaroglu (SILA SCIENCE, 2012)
Autism is defined as a pervasive developmental disorder which affects a child's communication, social interaction and behaviors. For some individuals oral communication is never established, because they can either not talk or refuse to talk. Education is the only proved way to help individuals with autism to cope with the social world around them; therefore besides their families, there need to be schools, administrators and teachers to help these individuals. The biggest problem about the education of individuals with autism is the lack of awareness in schools and in society at all. This paper includes a research study which investigates elementary school administrators' and teachers' perceptions on children with autism and their ways of handling the problems schooling. Results, based on data collected from one hundred seventeen administrators and teachers, indicate the present situation in the Anatolian side of Istanbul, Turkey. Although administrators and teachers both feel themselves insufficient in teaching and dealing with children with autism, they do not ask for help and in-service training about the issue. They argue that the necessity of extra payment need to be done for them if they include a child with autism in their classes.
Keywords: Autism; Developmental disorder; Special education; Teachers' perception; Administrators' perception; EARLY-CHILDHOOD; EDUCATION; CHILDREN; SKILLS; Education & Educational Research